Analisis Resepsi Pemilih Muda Terhadap Calon Legislatif 2024 Dari Kalangan Gen Z Di Kecamatan Cilengkrang Kabupaten Bandung - Suherman, Mochammad Alfiansyah; K, Abdul Fadli; Alwaton, Yogie (eProceedings of Management, 2024)
This study aims to analyze the reception of young voters from Gen Z towards the 2024 legislative elections inCilengkrang District. Using a qualitative approach through data collection with in-depth interview methods with 15informants who are young voters in Cilengkrang District. This research found that the position of public acceptancein Cilengkrang District according to 3 positions of acceptance of legislative candidates from Generation Z and theresults are dominated by the Dominant-Hegemonic position where the community agrees with the existence oflegislative candidates from Generation Z. The results showed that the position of community acceptance inCilengkrang sub-district towards legislative candidates from Gen Z is dominated by the Dominant Hegemonic positionbecause the community considers that Generation Z has great opportunities and ambitions to bring change to thefuture government. This research is expected to provide insights for political parties and campaign teams to developmore effective strategies in attracting support for Gen Z legislative candidates, as well as being a valuable source ofinformation regarding the public's assessment of Gen Z candidates. Keywords-gen z, young voters, 2024 legislative election, reception